From global to intra-regional tourism - Anders Steene (UTMS Journal of Economics, 2016)
Regardless of how society has evolved, travel and tourism have had a positive development since the end of Second World War. But now it seems that the perception of risk and danger is accentuated and the tourists choose destinations based on more safety and security for tourists. Risks often seem to be based on different global activities and actions from different groups, which the individual can not affect or influence over. These perceived risks thus affect the development of tourism and travel in a global perspective. This article would discuss the new threats to the global tourism due to the terrorist attacks that target different countries and in many cases the popular tourist destinations. With the result that travel has become more intra-regional again. The article makes a review of the slightly incomplete statistics available in the area and discuss possible strategies for overcoming the existing terrorist attacks. The conclusions of the article points to a more concrete cooperation between international and national organizations, governments, as well as NGOs, tour operators and civil society in general.
Keywords: Z3; 330; global; conflict zones; terrorism; civil war; intra-regional